AI-Personalized Ads and Indonesian Adolescents’ Buying Decisions - Windarsari, Wiwin Riski; Rostina (Malaqbi Publisher, 2025)
This qualitative study explores the profound influence of AI-powered personalized advertising on Indonesian adolescents' consumer decision-making. Situated within Indonesia's rapidly digitizing economy and collectivist cultural context, the research employed in-depth interviews and focus groups with 25 teenagers (aged 15-19) across urban and semi-urban settings. Findings reveal a complex interplay where algorithmic hyper-personalization creates a paradox of convenience and vulnerability, while teens appreciate ads that validating emerging identities, their fragmented understanding of cross-platform data tracking fosters passive resignation to surveillance. Crucially, personalized ads function as social catalysts shared within peer networks, they amplify Fear of Missing Out (FOMO) and transform purchasing into collective bonding rituals, intensifying pressure to conform. The frictionless path from personalized ad exposure to one-click purchases via integrated e-wallets frequently overrides deliberative decision-making, leading to impulsive spending and post-purchase dissonance, particularly among lower-SES youth. Despite emergent resistance strategies, a significant power asymmetry persists between sophisticated adtech and developing adolescent cognition. The study underscores an urgent need for contextual digital consumer literacy programs addressing algorithmic persuasion mechanisms and culturally responsive regulatory frameworks ensuring ethical AI deployment targeting minors. Protecting youth agency in Indonesia’s algorithm-driven marketplace demands recognizing personalized advertising not merely as commerce, but as a shaper of developmental trajectories and social relationships.